2016
DOI: 10.1038/srep22792
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cross-sectional imaging of the phonating larynx using long-range Doppler optical coherence tomography

Abstract: Diagnosis and treatment of vocal fold lesions has been a long-evolving science for the otolaryngologist. Contemporary practice requires biopsy of a glottal lesion in the operating room under general anesthesia for diagnosis. Current in-office technology is limited to visualizing the surface of the vocal folds with fiber-optic or rigid endoscopy and using stroboscopic or high-speed video to infer information about submucosal processes. Previous efforts using optical coherence tomography (OCT) have been limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Based upon system configuration, various low coherent near‐infrared light sources are used, including super luminescent diodes (SLD) and swept vertical cavity surface emitting lasers (VCSELs) . Various OCT probes and hand piece designs—including microscopes, rigid endoscopes, and flexible endoscopes—allow for forward viewing , side viewing , or rotary viewing . Using a TD system with a forward facing probe, Sergeev et al first demonstrated the feasibility of using endoscopic OCT to image the mucosa of various organs, including the larynx .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon system configuration, various low coherent near‐infrared light sources are used, including super luminescent diodes (SLD) and swept vertical cavity surface emitting lasers (VCSELs) . Various OCT probes and hand piece designs—including microscopes, rigid endoscopes, and flexible endoscopes—allow for forward viewing , side viewing , or rotary viewing . Using a TD system with a forward facing probe, Sergeev et al first demonstrated the feasibility of using endoscopic OCT to image the mucosa of various organs, including the larynx .…”
Section: Introductionmentioning
confidence: 99%
“…There are several OCT system configurations: time domain (TD), and Fourier domain techniques including swept source (SS) and spectral domain (SD) [8][9][10]. Based upon system configuration, various low coherent near-infrared light sources are used, including super luminescent diodes (SLD) [8] and swept vertical cavity surface emitting lasers (VCSELs) [11]. Various OCT probes and hand piece designs-including microscopes, rigid endoscopes, and flexible endoscopesallow for forward viewing [8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25], side viewing [11,[26][27][28][29][30][31][32], or rotary viewing [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) and high-frequency (>30 kHz) ultrasound provide high-resolution, cross-sectional imaging of tissues and have been used to evaluate naïve, pathologic and surgically manipulated vocal fold mucosae in preclinical models and human patients (Burns et al, 2011, 2009; Coughlan et al, 2016; Huang et al, 2007; Walsh et al, 2008; Wong et al, 2005). Imaging data are available in real time; however, with the exception of long-range OCT (Coughlan et al, 2016; Vokes et al, 2008), these techniques require endolaryngeal placement of an imaging probe used in contact or near-contact mode, have limited depth penetration and do not provide full anatomic context for the region of interest. Magnetic resonance imaging (MRI) is an alternative technology that allows high-resolution, high-contrast imaging of whole tissues.…”
Section: Introductionmentioning
confidence: 99%
“…*Correspondence to: Mette Pedersen, The Medical Center, Ear Nose Throat Unit, Oestergade 18, DK-1100 Copenhagen, Denmark, Email: m.f.pedersen@dadlnet.dk O ptical coherence tomography (OCT) is an imaging technology that provides cross-sectional images without biopsy of subsurface tissue structure at approximately 10-mm resolution to a depth of 1.5 mm using backscattered light. OCT has shown promise in imaging normal vocal folds as well as various laryngeal disorders (1). The use of OCT to image the larynx during diagnosis and treatment of a vast array of laryngeal disorders continues to develop along with innovative surgical techniques.…”
Section: In Contextmentioning
confidence: 99%